Kinetic Alfvén waves in three‐dimensional magnetic reconnection. Issue 7 (19th July 2016) - Liang, Ji; Lin, Yu; Johnson, Jay R.; Wang, Xueyi; Wang, Zheng‐Xiong
Abstract: Alfvénic waves are believed to be fundamentally important in magnetic reconnection. Kinetic dynamics of particles can break the Alfvén speed limit in the evolution and propagation of perturbations during reconnection. In this paper, the generation and signatures of kinetic Alfvén waves (KAWs) associated with magnetic reconnection in a current sheet is investigated using a three‐dimensional (3‐D) hybrid code under a zero or finite guide field. In order to understand the wave structures in the general cases of multiple X line reconnection, cases with a single X line of various lengths are examined. The KAWs are identified using the wave dispersion relation, electromagnetic polarization relations, as well as spectral analysis. In the cases in which the X line is so long to extend through the entire simulation domain in the current direction, quasi 2‐D configurations of reconnection are developed behind a leading flux/plasma bulge. KAWs with perpendicular wave number k ⊥ ρ i ∼1 (with ρ i being the ion Larmor radius) are found throughout the transient plasma bulge region and propagate outward along magnetic field lines with a slightly super‐Alfvénic velocity. These KAWs are generated from the X line and coexist with the whistler structure of the ion diffusion region under a small guide field. In the cases in which the X line has a finite length 2 ξ ∼ 10 d i, with ξ being the half length of the X line and d i the ion inertial length, the KAWs originated from the X line are of 3‐D nature. Under a finite guide field, KAWs propagate along the oblique magnetic field lines into the unperturbed regions in the current direction, carrying parallel electric field and Poynting fluxes. The critical X line length for the generation of 3‐D‐like structures is found to be 2 ξ c ≤30 d i . The structure, propagation, energy, spectrum, and damping of the KAWs are examined. Dependence of the structure of KAWs on the guide field is also investigated. Key Points: KAWs that propagate along the magnetic field are a common feature in reconnection with various X line lengths and guide field strengths Both KAWs and the whistler structures are generated from the X line Guide field strength plays an important role in determining the structure of the KAWs